INOVASI DIGITALISASI K3 DENGAN BIM 8D - Kartika Hapsari; Ariya Fawwas Hawari (Universitas Widyatama, 2026)
The use of Building Information Modeling (BIM) has proven to be highly beneficial for construction service providers in project planning and execution, including in the control of Occupational Health and Safety (OHS) risks. However, the adoption of BIM technology for OHS management is still uneven across construction companies, as seen in the BSD Grand Mosque Project. This research aims to develop an OHS risk control model using 4D BIM for the BSD Grand Mosque Project and to identify its advantages and shortcomings. The novelty of this study lies in the innovative development of on-site OHS monitoring through BIM visualization integration, as well as in-depth analysis of expert and worker perceptions regarding the effectiveness of BIM models for OHS. The research methods involve the creation of a 4D BIM model, innovation in BIM-based OHS risk control, and evaluation through interviews and questionnaires. The results show that the developed model is highly effective in hazard identification, risk visualization, accurate control planning, material arrangement, and on-site OHS monitoring. Nevertheless, there are shortcomings in the specification features of OHS equipment, which are not yet optimal and require further development, and many workers still lack a full understanding of BIM modeling.